THEORETICAL STUDY ON THE CRASHWORTHINESS OF CORRUGATED TUBE - ZHANG Ping; MA Jian; NA JingXin (Jixie qiangdu)
The energy absorbing property of corrugated tube subjected to axial crushing was researched through theoretical analysis. In view of the energy absorbing mechanism for axisymmetric deformation mode,a calculation formula for the mean crush load was put forward. It shows that the mean crush load is mainly influenced by the tube geometric parameters,material properties and loading rate. The theoretical analysis method was proved with the simulation results. Based on the theoretical analysis and numerical simulation effects of geometric parameters on the mean crush load were studied. Decreasing corrugation angle or increasing corrugation wavelength leads to accelerated increasing the mean crush load. Compared to the quasi-static crushing tests,the mean dynamic crush loads increase at about 80%. This work provides valuable theoretical guidance and design reference for the application of corrugated tube to structural crashworthiness field.